Contemporary Anticoagulation Reversal: Focus on Direct Thrombin Inhibitors and Factor Xa Inhibitors. (February 2013) - Mancl, Erin E.; Crawford, Alexis N.; Voils, Stacy A.
Several oral direct thrombin inhibitors (DTIs) and factor Xa (FXa) inhibitors have recent Food and Drug Administration approval or are under investigation in late-stage clinical trials for the prevention and treatment of thromboembolic events. Rapid reversal of anticoagulation is typically recommended in patients with severe or life-threatening bleeding and in patients requiring surgery or invasive procedures. However, no antidote exists for DTIs or FXa inhibitors though replacement of coagulation factors using clotting factor concentrates is routinely considered in some clinical scenarios. Clotting factor concentrates available in the United States include prothrombin complex concentrate, activated prothrombin complex concentrate, and recombinant factor VII, activated. Coagulation tests to confirm adequate reversal of anticoagulation should be considered and commonly include activated partial thromboplastin time and thrombin time (TT) for DTIs, and chromogenic FXa assay and TT for FXa inhibitors. Monitoring of coagulation tests should continue for 1 to 2 days after achievement of hemostasis, since the duration of the clotting factor concentrate may be shorter than the oral anticoagulant, especially in patients with organ dysfunction. Utilization of decision-support tools and use of standardized reversal protocols are recommended to prevent errors in prescribing and dispensing for clotting factor concentrates.